Broad‐scale distribution of diazotrophic communities is driven more by aridity index and temperature than by soil properties across various forests - Zhao, Wenqiang; Kou, Yongping; Wang, Xiaohu; Wu, Yanhong; Bing, Haijian; Liu, Qing; Soininen, Janne (Global ecology and biogeography, 2020)
Aim Many studies have found that diazotrophic distribution is mainly determined by soil properties from field to regional scales. However, we lack strong evidence for the relative importance of different drivers controlling broad‐scale biogeography of forest diazotrophs, especially for soil multi‐nutrients. Location China’s forests. Time period 2012−2013. Major taxa studied Diazotrophic communities. Methods We investigated the distribution of soil diazotrophic communities from 146 sites along a 3,900‐km south–north transect by sequencing N‐fixing nifH gene amplicons. The relative contributions of environmental variables were assessed using a combination of stepwise multiple regression, variation partitioning analysis, multiple regression on distance matrices and partial least squares path modelling. Results Overall, aridity index and temperature were the predominant parameters governing diazotrophic community diversity and structure, mainly through their indirect effects on soil pH, nutrient contents and plant productivity. Although soil multi‐nutrients (Ca, Mg, Fe, Mn, Na, Cu and Zn) were included in the statistical analysis, they still exhibited lower impacts on diazotrophic communities than climate. Intriguingly, the microelement Mo could not explain the diazotrophic community patterns, despite its significance in nitrogenase enzymes. This unexpected phenomenon was attributed to the relatively high Mo supply in our work. Moreover, the distinct responses of diazotroph taxa to climatic factors and large heterogeneity of diazotrophic diversity among forests in different climatic zones further support the dominant role of climatic variation. These results indicate the presence of differentiated climatic niches for diazotrophs, such as warm‐adapted Bradyrhizobium and cool‐adapted Azospirillum. Main conclusions Our findings suggest for the first time that unlike prior studies, the key roles of soil nutrient limitation (even for Mo) and pH‐dependent mechanisms in small‐scale diazotrophic communities can be surpassed by large‐scale climatic gradients. Future changes in drought severity and temperature might greatly shape diazotrophic distribution and its potential function in forest N2 fixation.